Antithrombotic Therapy in Patients With Atrial Fibrillation Undergoing Percutaneous Coronary Intervention: A North American Perspective—2016 Update. (November 2016) - Angiolillo, Dominick J.; Goodman, Shaun G.; Bhatt, Deepak L.; Eikelboom, John W.; Price, Matthew J.; Moliterno, David J.; Cannon, Christopher P.; Tanguay, Jean-Francois; Granger, Christopher B.; Mauri, Laura; Holmes, David R.; Gibson, C. Michael; et al.
Abstract : The optimal antithrombotic treatment regimen for patients with atrial fibrillation undergoing percutaneous coronary intervention with stent implantation is an emerging clinical problem. Currently, there is limited evidenced-based data on the optimal antithrombotic treatment regimen, including antiplatelet and anticoagulant therapies, for these high-risk patients with practice guidelines, thus, providing limited recommendations. Over the past years, expert consensus documents have provided guidance to clinicians on how to manage patients with atrial fibrillation undergoing percutaneous coronary intervention. Given the recent advancements in the field, the current document provides an updated opinion of selected North American experts from the United States and Canada on the treatment of patients with atrial fibrillation undergoing percutaneous coronary intervention. In particular, this document provides the current views on (1) embolic/stroke risk, (2) ischemic/thrombotic cardiac risk, and (3) bleeding risk, which are pivotal for discerning the choice of antithrombotic therapy. In addition, we describe the recent advances in pharmacology, stent designs, and clinical trials relevant to the field. Ultimately, we provide expert consensus–derived recommendations, using a pragmatic approach, on the management of patients with atrial fibrillation undergoing percutaneous coronary intervention.